2004
DOI: 10.1096/fj.03-1228fje
|View full text |Cite
|
Sign up to set email alerts
|

Disuse atrophy and exercise rehabilitation in humans profoundly affects the expression of genes associated with the regulation of skeletal muscle mass

Abstract: Skeletal muscle atrophy occurs as a consequence of injury, illness, surgery, and muscle disuse, impacting appreciably on health care costs and patient quality of life, particularly in the absence of appropriate rehabilitation. The molecular mechanisms that regulate muscle mass during atrophy and rehabilitation in humans have not been elucidated, despite several robust candidate pathways being identified. Here, we induced skeletal muscle atrophy in healthy volunteers using two weeks of limb immobilization, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
326
8
9

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(376 citation statements)
references
References 49 publications
33
326
8
9
Order By: Relevance
“…In contrast to data on CAPN1 and 2, mRNA levels for CAPN3 are down-regulated acutely in animal models of muscle wasting such as cancer 115 , and denervation 116 , and in human disuse atrophy 110 . However CAPN3 down-regulation may not be a universal occurrence in atrophying muscle as CAPN3 was not identified as a consistently regulated atrogene in other studies of gene expression in muscle atrophy 44 .…”
Section: Calpainscontrasting
confidence: 77%
See 1 more Smart Citation
“…In contrast to data on CAPN1 and 2, mRNA levels for CAPN3 are down-regulated acutely in animal models of muscle wasting such as cancer 115 , and denervation 116 , and in human disuse atrophy 110 . However CAPN3 down-regulation may not be a universal occurrence in atrophying muscle as CAPN3 was not identified as a consistently regulated atrogene in other studies of gene expression in muscle atrophy 44 .…”
Section: Calpainscontrasting
confidence: 77%
“…Thus myofibrillar-bound CAPN1 activity is increased early in electrical low frequency stimulation-induced fast-to-slow myofiber type transition, whereas preferential increases in CAPN2 myofibrillar-bound activity are seen in response to direct muscle injury 109 . Human gene expression studies showed no change in mRNAs encoding CAPN1, 2 and calpastatin as a result of disuse, but increases in all three genes were observed during remobilizing 110 . In addition other studies that have demonstrated increased calpain activity in human muscle after eccentric, i.e.…”
Section: Calpainsmentioning
confidence: 93%
“…Além disso, foi encontrado o valor médio de 2.574,88µm 2 para o músculo sóleo do grupo controle, estando de acordo com os valores de referência apresentados pela literatura, que podem variar de 2.084 a 3.500µm (17)(18)(19) . Com relação à área relativa do tecido conjuntivo intramuscular de músculos normais, a literatura apresenta valores de 1 a 10%, dependendo do músculo avaliado (19,20) .…”
Section: Discussionunclassified
“…Among the models of RE most commonly used in disuse atrophic states are flywheel (30)(31)(32)(33)(34), vascular occlusion (VO) (35), and conventional RE consisting of concentric/eccentric or isometric muscle actions (20,36,37). It is important to emphasize that the composition of these types of RE differs in terms of intensity and volume.…”
Section: Magnitude and Functionality Of Different Types Of Resistancementioning
confidence: 99%
“…They observed that the trained group showed significant preservation of femoral biceps and semitendinosus muscle CSA (corresponding to approximately 70% of the flexor muscles) compared to the untrained group. Jones et al (36) investigated the role of isokinetic knee extension for 6 weeks after 2 weeks of unilateral lower limb immobilization. After the immobiliza-tion period, the lean mass of the individuals presented a reduction of about 5%, which was restored after 6 weeks of RE.…”
Section: Conventional Resistance Exercise (Dynamic Eccentric And/or mentioning
confidence: 99%